Asymptomatic cerebral findings on 3-Tesla MRI in patients with severe carotid artery stenoses. (July 2022) - Komura, Shoichi; Nomura, Tatsufumi; Imaizumi, Toshio; Inamura, Shigeru; Kanno, Aya; Honda, Osamu; Hashimoto, Yuji; Mikami, Takeshi; Nonaka, Tadashi
Highlights: With differences between SVD and LVD, the prevalences of SVDs were associated with severe CA stenoses. SVD includes white matter lesions, LI and CMBs, however CMBs were not associated with severe CA stenoses. Hyperlipidemia related to atherosclerosis might reduce the prevalence of deep CMBs and mixed CMBs. Abstract: Background and purpose: Small vessel diseases (SVDs) are often asymptomatic. However, SVDs significantly influence the prognosis in patients with large vessel diseases (LVDs). We investigated asymptomatic cerebral findings on 3-Tesla MRI in patients with severe carotid artery (CA) stenoses, compared to peoples without a past history of neurological disorders, including strokes. Methods: We retrospectively analyzed the prevalences of various asymptomatic cerebral findings which were intracerebral hemorrhages (ICHs), cortical superficial siderosis, ventricular dilatation (Evans' index) and SVDs including cerebral microbleeds (CMBs), lacunar infarctions (LIs), deep white matter hyperintensities (WMHs), periventricular hyperintensities (PVHs). The prevalence of each finding was compared using multivariate logistic regression models with adjustment for stroke risk factors. Results: We evaluated the findings in 54 patients with severe CA stenosis treated by stenting (CA stenosis group) and 200 adults with health screening tests of the brain and no past history of neurological disorders (control group). Multivariate analyses adjusted for age ≥ 65 years old, female gender, hypertension, hyperlipidemia, diabetes mellitus, alcohol consumption, and smoking index revealed that the prevalences of severe PVHs, severe deep WMHs, asymptomatic deep ICHs, and asymptomatic LIs were significantly higher in the CA stenosis group than the control group. However, there were no significant differences in the prevalences of CMBs, or the remaining asymptomatic findings described above. Conclusions: With pathological differences between SVD and LVD, asymptomatic SVDs except CMBs and deep ICHs often co-exists severe CA stenosis as a presentative LVD.